Funerary practices in the Czech Republic - Nešporová, Olga (Funerary international, 2020)
Exploring the traditions, customs and contemporary legal framework of Czech funerary practices, this book analyses and interprets the high cremation rate, predominance of secular funerals and increasing popularity of cremation with no funeral ceremony against the background of the country's historical development.